Pengaruh Pengawasan Kerja, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Kecamatan Penjaringan Jakarta Utara - Fadil Syafii; Rudi Kristanto (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
Every organization tries to achieve its goals by using all the human resources it has. Therefore, the goals of each human resource in the organization must be maintained in line with the goals of the organization. In addition, human resources in the organization are expected to have the competence, abilities, and skills needed to carry out their duties. The organization also needs human resources who have achievement motivation and work ethic and no less important is a strong commitment to the organization. Thus, it is expected that the organization's human resources can provide the best contribution to the organization. The concept of performance management is one of the important developments in the scope of management. Performance management began to take shape in the late 1980s, developing from the awareness of the need for a more focused and sustainable approach to managing and rewarding performance. Often, a performance appraisal system and salary/wage determination linked to performance are developed in an unsystematic manner and implemented incorrectly so that they do not provide the expected results. This study uses quantitative descriptive, with a population of 41 employees of the Penjaringan District office and uses saturated samples because the population is below 100. The sampling technique uses a negative 5-interval Likert scale. The results of this study produce , t-test, that work supervision, work discipline and work environment each have a positive effect on employee performance, while the f-test, shows the results that work supervision, work discipline and work environment together affect employee performance by 91.3% and the coefficient of determination in this study is 8.7%.